Development of Emulsified Wastewater Treatment System - Mohd Najib, Razali (2014)
This work targets to develop an emulsified wastewater treatment system. It was done by employing low cost biomaterials chitosan and rubber seed shell activated carbon (RSSAC) as coagulant and adsorbent respectively. RSSAC was prepared by chemical activation at different carbonization temperatures. The highest BET surface area (SBET) generated was at 650°C. The higher the temperature, the higher the SBET until it reaches 850°C where the SEET starts to decline due to rupture of some porous walls. The industrial emulsified wastewater was treated using chitosan versus chitosan + RSSAC combined by varying the mixing time and dosage. Percentage removal of oil & grease (O& G), total suspended solids (TSS), turbidity and pH were investigated by comparing chitosan and chitosan + RSSAC with the emulsified wastewater. The combined treatment able to reduce the O& G at 90% compared to 76% by chitosan alone. This may be because chitosan promotes the coalescence by breaking of majority of the oil droplets while RSSAC adsorbs the residual oil. The TSS was greatly reduced up to 99.5% by chitosan and 98.7% by combined treatment. Besides that, both treatments were able to reduce the turbidity up to 98.5% for chitosan and 92.5% for combined treatment. The pH was reduced from 9.71 to 8.88 and 8.82 after treatment. There was not much difference in pH reduction from either of the treatment methods. pH value may be said to have negligible effect in O& G and other parameters removal efficiency in this work At pH higher than 7.5, chitosan losses it's solubility and able to promote phase separation of O/W emulsions (Bratskaya et at, 2006). At the present work, chitosan is able to separate the oil residue at pH 9.71. All in all, RSSAC may be further used as high effective bio-adsorbent to adsorb other types of substances such as dye, heavy metals and impurities. The present work concludes the promising future of biomaterials as an effective coagulant and adsorbent for emulsion waste treatment.